Modeling of the process approach to the life cycle of measuring instruments - Velychko, Oleh; Hrabovskyi, Oleh; Gordiyenko, Tetyana; Volkov, Serhii (Eastern-European Journal of Enterprise Technologies, 2021)
The problem of increasing the reliability and competitiveness of products in all sectors of the national economy can be solved only on the basis of obtaining complete and reliable measurement information. This is facilitated by modern measuring instruments (MI), which are complex hardware and software systems. The relevance of the study is due to the fact that modern MI need an effective assessment of their quality at all stages of the life cycle (LC). This requires the development of appropriate assessment methods both at the stage of production and operation of MI. The expediency of using the process approach to MI LC stages and its advantages over the functional approach were proved. The process approach allows more effective assessment of MI quality indicators at different LC stages and is compatible with the construction of modern quality management systems. Mathematical modeling was carried out, a set process model of the MI LC was developed and its representation as a process V-model was carried out. This allows studying the interaction of processes of all MI LC stages and performing process quality management at all MI LC stages. Mathematical modeling was carried out, a set process model of evaluation of quality indicators of MI LC stages was developed and its representation as a process V-model was carried out. This allows evaluating quality indicators of the MI and its components throughout the MI LC. Recommendations for the use of international standards were formulated, in particular for project management planning, measurement processes, system requirements throughout the MI LC, risk analysis and management at the LC stages. This should help increase efficiency in achieving the planned results at all stages of the MI LC